369 Acute effects of occupational noise exposure on 24-hour ambulatory blood pressure in workers with hypertension. (11th October 2013) - Chang, T Y; wang, H; Liu,; sieh, H; Bao,; Lai,
Abstract : Objectives: Hypertension is the prevalent disease in the workplace. Although the elevation of blood pressure from exposure to occupational noise has been recognised, research on susceptibility to occupational noise exposure in adults with hypertension is not reported. This repeated-measure study investigated the effects of occupational noise exposure on 24-hour ambulatory blood pressure in a cohort with hypertensive and normotensive workers. Methods: We enrolled 117 volunteers in an aircraft-manufacturing industrial cohort followed from 1998 to 2008. Individual noise exposure and personal blood pressure were determined simultaneously over 24 hours in 19 hypertensive and 98 normotensive workers during the working and non-working days. Linear mixed-effects regressions were used to investigate the effects of noise exposure on ambulatory systolic blood pressure (SBP) and diastolic blood pressure (DBP) between two groups during different periods by controlling for potential confounders. Results: Hypertensive workers had significantly higher mean values of ambulatory SBP (12.6 [95% confidence interval: 10.3–15.0] mmHg; 10.3 [7.8–12.8] mmHg) and DBP (8.0 [6.3–9.7] mmHg; 7.2 [5.3–9.1] mmHg) compared with normotensive workers on both working and non-working days. Such differences between two groups were obviously higher on the working day than on the non-working day. Per one A-weighted decibel (dBA) increase in the 24-hour average noise exposure was significantly associated with transient elevations of SBP (0.25 [0.15–0.36] mmHg) and DBP (0.16 [0.09–0.23] mmHg) among hypertensive workers on the working day. Such effects on SBP and DBP still persisted at the 60-min time-lagged noise exposure and the increases of SBP were more pronounced in the hypertensive group than in the normotensive group. Conclusions: Hypertensive workers are more susceptible to noise exposure, especially the effect on ambulatory SBP. These results suggest a need for the more protection to the susceptible population.